KONFLIK MONYET EKOR PANJANG (Macaca fascicularis) DAN MANUSIA PADA BERBAGAI TIPE PENGGUNAAN LAHAN DI SUAKA MARGASATWA PALIYAN DAN SEKITARNYA - , BAMBANG WIDIATMOKO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research has aims to determine (1) the population and distribution of long-tailed macaque (Macaca fascicularis) in Paliyan Wildlife Sanctuary, (2) biotic and abiotic characteristics Mof the location in various type of land use in Paliyan Wildlife Sanctuary and its surrounding, (3) the conflict characteristics of long-tailed macaque (Macaca fascicularis) and human in Paliyan Wildlife Preserve and its surrounding. The research sites were in Paliyan Wildlife Preserve. Karang Asem, Karang Duwet Village (Paliyan District)